Analisis Beban Kerja untuk Mengoptimalkan Jumlah Tenaga Kerja dengan Menggunakan Metode Workload Analysis - Pranasyarif, Laudaffa; Sudiana, Kiki (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the workload on the Primary & Secondary Education Operation, Control and Evaluation (PSE OCE) division at Yayasan Pendidikan Telkom. Workload analysis in this study uses the FTE (Full-Time Equivalent) method to analyze workload. The Full-Time Equivalent method used found that there were 1 person with an FTE score > 2.5. The final score for the total workload received by the permanent employees of the PSE OCE division is 7.555471124. So management should add 3 more people so that the existing workload can be optimal. Keywords: Full-Time Equivalent, Optimal Number of Employees, Workload, Workload Analysis